2016
DOI: 10.1007/s00404-016-4150-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological aspects of cystocele with a 3D finite elements model

Abstract: A 3D digital model enabled simulations of anatomic structures underlying cystocele to better understand cystocele pathophysiology. The model could be used to predict cystocele surgery results and personalising technique by preoperative simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…Through representing a different physiopathological situation, a similar effect of the fascia impairment has been recently observed for the phenomenal development of the cystocele. Symptoms are dramatic after 40% impairment of the pubocervical fascia [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Through representing a different physiopathological situation, a similar effect of the fascia impairment has been recently observed for the phenomenal development of the cystocele. Symptoms are dramatic after 40% impairment of the pubocervical fascia [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…This approach allows moving towards the patient‐specific treatment. Indeed, this work based on medical imaging and numerical simulation would make it possible to better understand pelvic mobility and to study the potential defects related to the equilibrium of pelvic statics . The care can be adapted more precisely to the pathology in a specific way using a numerical FE model.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Therefore, most of the key repairable structures of pelvic oor support are pubocervical fascia and uterosacral ligaments, which are located above levator ani muscle level, i.e., level I and II repair. A 3D digital model showed that pubocervical fascia is the most in uential structure in the onset of the median cystocele [12]. Accordingly, we attempted to reconstruct the pubocervical fascia and x it intraoperatively on the vaginal stump.…”
Section: Sacrospinous Ligament Xation (Sslf)mentioning
confidence: 99%